2016
DOI: 10.1007/s12035-016-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Link Between Fkbp5/FKBP5, Early Life Social Relations and Alcohol Drinking in Young Adult Rats and Humans

Abstract: Alcohol misuse has been linked to dysregulation of stress, emotion, and reward brain circuitries. A candidate key mediator of this association is the FK506-binding protein (FKBP5), a negative regulator of the glucocorticoid receptor. The aim of the present study was to further understand the Fkbp5/FKBP5-related genetic underpinnings underlying the relationship between early life social relations and alcohol drinking. The effect of maternal separation and voluntary alcohol drinking on Fkbp5 expression was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 69 publications
3
19
0
Order By: Relevance
“…The present study identified 129 genes (FDR < 0.05) that were differentially expressed in alcohol dependent subjects (Supplementary table 1). FKBP5, a well studied gene that is asoociated with alcohol use [28][29][30][31] , showed increased expression in the PFC of alcohol dependent subjects in our differential gene expression analysis (l 2 FC 0.27; P = 4.57 x 10 -7 ). Other studies have also shown that FKBP5 plays a role in alcohol drinking behaviors in rodents 28,29 and humans 32 .…”
Section: Discussionmentioning
confidence: 70%
“…The present study identified 129 genes (FDR < 0.05) that were differentially expressed in alcohol dependent subjects (Supplementary table 1). FKBP5, a well studied gene that is asoociated with alcohol use [28][29][30][31] , showed increased expression in the PFC of alcohol dependent subjects in our differential gene expression analysis (l 2 FC 0.27; P = 4.57 x 10 -7 ). Other studies have also shown that FKBP5 plays a role in alcohol drinking behaviors in rodents 28,29 and humans 32 .…”
Section: Discussionmentioning
confidence: 70%
“…The FKBP51 antagonist, SAFit2, was synthetized as described previously . For intraperitoneal injections, SAFit2 was solubilized in vehicle consisting of 4% EtOH, 5% Tween80, and 5% PEG400 in 0.9% saline.…”
Section: Methodsmentioning
confidence: 99%
“…For intraperitoneal injections, SAFit2 was solubilized in vehicle consisting of 4% EtOH, 5% Tween80, and 5% PEG400 in 0.9% saline. SAFit2 and vehicle were administered 12 hours and 1 hour before testing as short and long latency effects on emotional behavior had been reported . The plasma half‐life of SAFit2 is 9.7 hours after intraperitoneal application in mice and robust high plasma levels are achieved during sub‐chronic dosing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations